Application of Double Width Seismic Data to Channel Sand Body Prediction of X Gas Field in the East China Sea - Wei HU; Dewen QIN; Qin LI; Weizhe YU; Jun HUANG (CT Lilun yu yingyong yanjiu, 2022)
Due to that the main reservoirs of the X gas field in the East China Sea were deeply buried and have large lateral changes, the conventional seismic data resulted in poor quality and low resolution, which couldn’t meet the increasingly refined geological requirements in exploration and development. Seismic data with wideband and wide azimuth was obtained by using the acquisition method of three ships and four sources with oblique cables, which held the characteristics of high resolution, high signal-to-noise ratio and high fidelity. By taking advantage of the superior information of wideband and wide azimuth seismic data which was high-resolutional and anisotropic, combined with the simultaneous prestack inversion, the inversion body of sensitive elastic parameters of channel sand bodies in different azimuths can be obtained, and superimpose multiple azimuth inversion bodies perpendicular to the direction of the river channel to carry out fine predictions of channel sand bodies. Compared the conventional seismic data, reservoir inversion based on wideband and wide azimuth seismic data improved the prediction accuracy of channel sand bodies, laying a foundation for the progressive exploration and development of the X gas field in the East China Sea.